1994
DOI: 10.1002/ijc.2910570115
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of retinoids and interferon α on tumor‐induced angiogenesis: Anti‐angiogenic effect on HPV‐harboring tumor‐cell lines

Abstract: Various retinoids and interferons exert anti-tumor effects both in experimental studies and in clinical trials. Recent reports indicate that they have a synergistic antineoplastic activity. Our study aimed to determine whether these synergistic anti-tumor effects are related to inhibition of tumor-cell-induced angiogenesis. A further aim was to compare the anti-angiogenic activity of various retinoids including 9-cis retinoic acid, a ligand for nuclear retinoic acid receptor RXR, given alone and in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(46 citation statements)
references
References 16 publications
2
44
0
Order By: Relevance
“…Indeed, Majewski et al 51 showed antiangiogenic activity of retinoids in a mouse model of tumorinduced angiogenesis and Pienta et al 52 demonstrated that HPR is a potent inhibitor of prostate cancer and EC growth in vitro and inhibits angiogenesis in the CAM assay.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Majewski et al 51 showed antiangiogenic activity of retinoids in a mouse model of tumorinduced angiogenesis and Pienta et al 52 demonstrated that HPR is a potent inhibitor of prostate cancer and EC growth in vitro and inhibits angiogenesis in the CAM assay.…”
Section: Discussionmentioning
confidence: 99%
“…Antiangiogenic effects of IFN (α, β, or γ) have also been observed in different clinical circumstances. 47,48 Quantifying Immune Therapy Benefit…”
Section: Subcutaneous Il-2mentioning
confidence: 99%
“…Initially, the direct cytostatic effect of IFN-a was thought to be the major mechanism by which it inhibits tumor growth (33,34,48); however, subsequent studies revealed that inhibition of angiogenesis and induction of tumor cell apoptosis are other IFN-a mediated antitumor effects (7,10,(49)(50)(51)(52). Our in vitro studies revealed that B16F10 melanoma cells are more sensitive to the cytostatic effects of IFN-a, whereas the CT26 colon carcinoma cells are more sensitive to the proapoptotic properties of rmIFN-a in vitro.…”
Section: Discussionmentioning
confidence: 99%